Chapter Migranti e rappresentazioni. Linguaggio, integrazione, discriminazione - Pezzoli, Silvia (Studi e saggi, 2021)
Public discussion on migration is addressed through frame and signification processes in which journalistic production plays a crucial role. Compared to the past, more diversified and articulated frames are adopted in the current representation of migration. Publics grassroots productivity goes along and overlaps with journalistic contents. The chapter aims to investigate how discussion on migration develops, with a focus on the innovations introduced by digital technologies and social web and the new possibilities for access, participation and production of contents by the audience.